Mobilização de atores sociais em rede: uma análise sobre a capacidade de organização da sociedade para enfrentamentos socioambientais - Almeida, Ricardo (2019)
Studies in Science, Technology and Society (STS) arose amid questions about the role of science and the use of technology in society, and its main purpose is to elucidate theories and methods that address the relationships between these three strands. One of the issues that raises the most concern in the scientific community, and affects society as a whole, concerns social and environmental problems, which are taking on increasing proportions even though there are legal provisions to mitigate them. In this arrangement of intense relationships, involving society and the environment, an important theory of the STS field arises that discusses the mutual influence exerted by human and non-human actors: the Actor-Network Theory, whose precursor is Bruno Latour. Supported by this theory and guided by the guidelines of a Brazilian Environmental Education program, this research proposes the formation of a network of social actors to face social and environmental challenges in a community in the city of Uberaba, located in Minas Gerais State, Brazil, in which society is invited to reflect on their reality and to act on relevant issues that impact its environment. The main objective of this study was to characterize the role of these actors in conducting the desired transformations, taking a close look at the organizational capacity of society during the confrontations. Based on the participatory action research methodology, network mediations were constituted by the stages of diagnosis, social mobilization and field intervention, involving community, schools, churches, universities, cooperatives, public authorities, among other agents. The results indicated that although society has the potential to overcome socio-environmental challenges, it is still unable to perpetuate the necessary transformations due to its dependence on government initiatives that, in turn, do not prioritize collective and participatory actions focused on socio-environmental confrontations. In addition, another aggravating scenario refers to environmental education, which is largely characterized by pragmatic actions, with little investment in actions based on critical thinking. In view of this, it can be concluded that although society is aware of the social and environmental challenges, its organizational capacity to face them requires, on the one hand, further dialogue between social actors and, on the other, educational processes that contemplate historical contexts about the social and environmental crisis and encourage the exercise of social control.